The significance of c.690G>T polymorphism (rs34529039) and expression of the CEBPA gene in ovarian cancer outcome - Konopka, Bozena (Oncotarget, 2016)
The CEBPA gene is known to be mutated or abnormally expressed in several cancers. This is the first study assessing the clinical impact of CEBPA gene status and expression on the ovarian cancer outcome. The CEBPA gene sequence was analyzed in 118 ovarian cancer patients (44 platinum/cyclophosphamide (PC)-treated and 74 taxane/platinum (TP)-treated), both in tumors and blood samples, and in blood from 236 healthy women, using PCR-Sanger sequencing and Real-Time quantitative PCR (qPCR)-based genotyping methods, respectively. The CEBPA mRNA level was examined with Reverse Transcription quantitative PCR (RT-qPCR). The results were correlated to different clinicopathological parameters. Thirty of 118 (25.4%) tumors harbored the CEBPA synonymous c.690G>T polymorphism (rs34529039), that we showed to be related to up-regulation of CEBPA mRNA levels (p=0.0059). The presence of the polymorphism was significantly associated with poor prognosis (p=0.005) and poor response to the PC chemotherapy regimen (p=0.024). In accordance, elevated CEBPA mRNA levels negatively affected patient survival (p<0.001) and tumor response to the PC therapy (p=0.014). The rs34529039 SNP did not affect the risk of developing ovarian cancer. This is the first study providing evidence that the c.690G>T, p.(Thr230Thr) (rs34529039) polymorphism of the CEBPA gene, together with up-regulation of its mRNA expression, are negative factors worsening ovarian cancer outcome. Their adverse clinical effect depends on a therapeutic regimen used, which might make them potential prognostic and predictive biomarkers for response to DNA-damaging chemotherapy.